PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER DAN PENCEGAHAN TINDAKAN BULLYING DI PONDOK PESANTREN AL HASSAN REMBANG - Choirul; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
Islamic education in character building of students is integrated in rational and mental movements, namely through changes in the way of thinking, acting, and behaving. The main values ​​that are the basis for character education include faith, noble morals (akhlak karimah), discipline, simplicity, and knowledge. Children who have strong characters tend not to commit negative actions such as bullying, which often occurs in schools and Islamic boarding schools. For example, students who have mental weaknesses are often the target of ridicule, insults, and even physical violence. Therefore, caregivers and administrators of Islamic boarding schools need to take an active role in dealing with this kind of problem. This study uses a qualitative approach with several techniques, such as data collection, data analysis, documentation studies, and direct observation. Informants in this study include the Islamic boarding school, caregivers, ustadz and ustadzah, administrators, and a number of students at the Al Hassan Rembang Islamic Boarding School. The results of the study show the importance of character building in students or students as an effort to prevent bullying behavior. The caretakers and administrators of Islamic boarding schools have implemented several character strengthening steps, including: (1) requiring discipline in attitudes and behavior, (2) teachers consistently providing advice to students, (3) giving sanctions as a form of guidance, and (4) providing motivation to encourage positive development. The prevention strategies for bullying behavior include: (1) applying punishment as a deterrent, (2) getting used to being friendly and polite, and (3) being an example from educators as a good example.